The Application of Literary Maps to the Teaching of English and American Literature in the Age of Big Data and the Internet of Things. (26th April 2022) - Chen, Binfeng
Abstract : The concept of the Internet of Things has had a dramatic impact on the traditional way of life of human beings since its birth. This shock has almost spread to education, medical, and other fields. It is reflected in the teaching process of English and American literature in colleges and universities, which greatly enhances the vividness of teaching and makes rigid knowledge memory more vivid and specific. Literary maps, as an important entry point for regional research on the development of literature, are playing an increasingly important role in the teaching of English and American literature. This paper studies the role of literary maps in British and American literature in order to improve students' ability to study British and American literature and promote the development of teaching. This paper mainly uses the experimental method and the investigation method to analyze this in detail and gets the concrete result. The data shows that literary maps play a certain role in structure, positioning, and empathy. All aspects are supported by nearly 25%. Therefore, the study of literary maps still has a significant impact on the teaching of English and American literature.